Development of nano-sized ketoprofen lysine incorporated Eudragit® S100 nanomedicine by double emulsion solvent evaporation and in vitro characterization. - A. Alper Öztürk; Nur İlge Çinar; Evrim Yenilmez (GarVal Editorial Ltda., 2019)
Context: Pain has a very important effect on the biological, psychological, sociological and economic situation of a patient. Nanoparticles (NPs) are being extensively investigated as drug delivery systems worldwide for pharmaceutical applications. Aims: To design and compare the release characteristics of sustained-release formulations of ketoprofen lysine (KL) NPs. Methods: KL-Eudragit® S100 NPs were produced by double emulsion solvent evaporation method. The physicochemical characteristics of NPs were studied. Results: Particle size of NPs prepared was in the range of 99 and 141 nm. Encapsulation efficiency (%) was obtained (76%) for NP formulations prepared. Weibull models were determined to be the most appropriate kinetic models for NP containing KL. KL-loaded NPs demonstrated nanostructural character and NPs showed extended release of KL. Conclusions: NPs developed were found to be stable and representing a promising system for sustained delivery of KL.